Authority of Notary To Make A Declaration As A Condition For Anyone To Be An Organ Recipient / Recipient - Anita Christiana; Moh Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
life of a human being is very valuable, as an effort to save someone from a disease or any cause, the method of organ transplantation is used which is a medical action based on religious, social, cultural values ​​while still referring to the rule of law. The rules regarding organ transplants have been regulated in statutory regulations to ensure legal certainty for the implementation of organ transplants and to avoid things that are against the law. Legislations give authority to notaries in making deed of statements as a prerequisite for registering prospective recipients. There are legal issues that can be drawn from this problem, namely the legal aspects of transplanting human organs and their supervision based on statutory regulations and the authority of a notary in making a statement deed as a prerequisite for someone to become a recipient. This type of research in legal research is normative legal research, which is a process to find legal rules, legal principles, and legal doctrines in order to answer legal issues at hand. The results of the study require a statement deed for prospective recipients, so both recipients and donors are expected not to provide funds and not make other agreements, this is purely a form of help.